Ultrasonographic Measurement of Optic Nerve Sheath Diameter for Detection of Raised Intracranial Pressure in Critically Ill Patients; A Novell, Non-Invasive and Point of Care Test - Khan, Rahmat Ullah; Sikandar, Rana Imran; Khurshid, Najma; Shafi, Salman; Bari, Abdul; Memon, Muhammad Iqbal (Pakistan Armed Forces Medical Journal, 2025)
Objective: To determine the diagnostic accuracy of bedside Ultrasonographic measurement of Optic Nerve Sheath Diameter for detection of raised Intracranial Pressure in critically ill patients in comparison with CT scan brain.Study Design: Prospective longitudinal studyPlace and Duration of Study: Department of Anesthesia and Critical Care Medicine, Pakistan Institute of Medical Sciences, Shaheed Zulfiqar Ali Bhutto Medical University Islamabad, Pakistan from Jun to Nov 2019.Methodology: Patients with clinical suspicion of raised ICP underwent Ultrasonographic measurement of ONSD by Principal Investigator within one hour prior to shifting of the patients to Radiology suite for CT scan brain to prevent diagnosis bias. The Ultrasonographic measured ONSD value of 5.0 mm was the cutoff limit for detecting raised ICP in our study. The CT scan brain reports were considered positive if findings suggested radiological features of raised ICP like Cerebral edema/effacement of ventricle or cisterns, midline shift or sub arachnoid haemorrhage. The diagnostic accuracy of Ultrasonographic measurement of ONSD for detection of raised ICP was then determined by comparing the results with radiological diagnosis of raised ICP by CT scan brain.Results: We enrolled total 120 patients in this study. The patients included in our study were suffering from different diseases like Traumatic Brain Injury (TBI), Meningitis, Encephalitis, Space Occupying Lesions (SOLs), Eclampsia, Stroke and Metabolic encephalopathy with different percentages. The ultrasonographic measured ONSD value range was from minimum 4.7 to maximum 6.9 with mean value of 6.1 mm. The sensitivity was 95.5%, specificity 91.3%, positive predictive value 93.2%, negative predictive value 98.5% where ultrasonographic measured ONSD value of 5.0 mm was taken as a cutoff limit. In our study ultrasonographic measured ONSD values showed good diagnostic accuracy for raised ICP detection in comparison with CT scan brain.Conclusion: We found that ONSD measured through bedside ultrasound is very useful for diagnosis and risk stratification of incipient intracranial hypertension in pregnant patients with pre-eclampsia and eclampsia where invasive monitoring is hazardous due to deranged coagulation profile.